Mecanismos n\~ao-lineares de repasse cambial para o IPCA - Dionísio Dias Carneiro; André Monteiro d'Almeida Monteirof; Thomas Yen Hon Wu (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
– This paper explores two changes in traditional models that measure the exchange rate pass-through in Brazil. The first change is a non-linear specification to the pass-through coefficient, making it depend on other variables that reflect economic conditions. The second change is to consider different components of the consumer price index, in search for transmission mechanisms of the exchange rate pass-through to prices. The empirical evidence obtained in the period between the quarter of 1994 and the last quarter 2001 suggests the existence of different non-linear mechanism among different price groups.
Keywords: E52; 330; Exchange Rate Pass-Through; Brasilien